Effect of modified starch used alone or in combination with wheat flour on the sensory characteristics of beef sausage - Mohammadi, Mehrdad; Oghabi, Firouz; Neyestani, Tirang-Reza; Hasani, Iman (Archives of Advances in Biosciences, 2013)
The effects of modified waxy maize starch (MWMS) (1–3.25%) on the sensory characteristics of 60% beef sausages were investigated by replacing the varying levels of sunflower oil or both sunflower oil and wheat flour (WF). The addition of MWMS improved the red color, the palatability, and the overall acceptability compared to the control sausages. The Color was medially and positively correlated with firmness. The correlations between color and taste and between taste with juiciness and firmness were weak and positive. The significant correlations were not observed between palatability and overall acceptability and with the other sensory characteristics. Juiciness was negatively correlated with firmness but was not significantly different. As a result, MWMS offset the effects of lowering the fat content.